Nurses' Knowledge, Attitude and Performance Towards the Principles of Islamic Ethics in Nursing Care in Tehran University of Medical Sciences - Jayran Zebardast; Nikzad Eisazadeh; Khorshid Vaskoei Eshkevari; Abolalfath Ghafari; Fatemeh Mirbazegh (Tehran University of Medical Sciences, 2018)
Background and Aim: Nurses' knowledge, attitude and performance towards the principles of Islamic ethics are remarkable in nursing care in Tehran University of Medical Sciences (TUMS).  Materials and Methods: In this cross-sectional study, the knowledge, attitude and performance of 551 nurses were evaluated based on their age, sex, education, and type of employment in TUMS hospitals (by a valid questionnaire). All data were analyzed by SPSS. In this study, a questionnaire was designed through a Focus group discussion and then its validity was evaluated. Moreover, the reliability of the questionnaire was estimated by test-retest method.     Results: Our study showed that female sex, work experience of 15-20 years, type of employment, and higher education were associated with a higher level of knowledge, attitude and performance towards principles of Islamic ethics. Also, according to our analysis, there was a significant relationship between age and level of knowledge, attitude and performance of the principles of Islamic ethics (p<0.05)  especially at the age of 40chr('39')s.   Conclusion: Based on the results of this study, there is a significant relationship between educational indices and work experience, and the age of nurses with the level of knowledge, attitude and practice regarding the principles of Islamic ethics. It is suggested that educational courses about Islamic ethics be presented based on nurses' educational levels and age.